2014
DOI: 10.1177/1045159514522433
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Students’ Perspectives on Effective Teaching

Abstract: This study employed data collected over an 8-year period in which graduate students’ perspectives on effective teaching were collected during a class exercise. The data were organized into three categories: (a) teaching competence (knowledge of content and teaching), (b) relationships with students (having the best interests of students at heart), and (c) teacher attitudes (with respect to teaching and learning). Students appear to concur with the literature in adult and higher education that effective teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
4
22
0
1
Order By: Relevance
“…Our participants described learning environments in which instructors shared enthusiasm, love, motivation for content, learning, and personal experiences. These findings are consistent with those from other researchers who identified that establishing a safe, supportive space for discussion is paramount for teaching and learning (Hill, 2014). However, a few participants perceived a lack of care from professors who were unprepared to teach and who did not value student learning.…”
Section: Assessing Teaching Effectivenesssupporting
confidence: 88%
See 3 more Smart Citations
“…Our participants described learning environments in which instructors shared enthusiasm, love, motivation for content, learning, and personal experiences. These findings are consistent with those from other researchers who identified that establishing a safe, supportive space for discussion is paramount for teaching and learning (Hill, 2014). However, a few participants perceived a lack of care from professors who were unprepared to teach and who did not value student learning.…”
Section: Assessing Teaching Effectivenesssupporting
confidence: 88%
“…Finally, a participant who appeared upset and disappointed with some instructors' teaching styles offered the following comments about an instructor who read PowerPoint slides verbatim in class: "I didn't like it only because I feel that I can read them [PowerPoint One important finding is that relationships between instructors and students are important, which is similar to other researchers' findings on the relationship among care, rapport, and student learning (Malott et al, 2014). Hill (2014), who conducted a study regarding graduate students' perspectives on effective teaching, said, "What is most important seems to be forming a relationship with students and caring about their learning" (p. 58). To establish positive relationships with students, instructors need to create a safe environment that involves care, respect, safety, and flexibility (Hill, 2014;Vella, 2002).…”
Section: Assessing Teaching Effectivenesssupporting
confidence: 62%
See 2 more Smart Citations
“…Specifically, Buller (2016) explored the experiences of award‐winning teachers in counselor education and identified seven common themes: (a) pride in teaching, (b) care, (c) challenge students, (d) authenticity, (e) passion for teaching, (f) organization, and (g) creativity. Additionally, Hill (2014) explored graduate students’ perceptions of educator effectiveness and identified three major themes regarding positive student experiences: (a) relevant knowledge of content; (b) genuine relationships with students characterized by respect, fairness, and flexibility; and (c) teachers’ attitudes toward teaching and learning, which included enthusiasm for the subject matter, compassion, and empathy for students. Moreover, in examining counselor education students’ experiences, researchers found that students rated instructor knowledge of content and delivery style (i.e., the ability to maintain students’ attention and interest in learning) as twice as important in evaluating teacher effectiveness compared with organization and workload for the course (Pietrzak, Duncan, & Korcuska, 2008).…”
mentioning
confidence: 99%